Bone stromal cells in pagetic bone and Paget's sarcoma express RANKL and support human osteoclast formation. - Sun, S; Lau, Y; Itonaga, I; Sabokbar, A; Athanasou, N (2006)
Paget's disease is a focal disorder of bone remodelling, in which there is an increase in osteoclast formation. A rare complication of Paget's disease is the development of a sarcoma, most commonly an osteosarcoma. Osteoclast formation occurs in the presence of macrophage-colony stimulating factor and receptor activator for nuclear factor-kappaB ligand (RANKL), and it has been shown that bone stromal cells in Paget's disease can influence osteoclast formation by modulating the expression of RANKL and its decoy receptor, osteoprotegerin (OPG). In this study we show that pagetic bone stromal cells express RANKL and that these cells promote osteoclast formation by a RANKL-dependent mechanism. Osteoclast formation in co-cultures of monocytes and either pagetic bone stromal cells or Paget's sarcoma stromal cells was not only induced by a contact-dependent mechanism but also occurred via the release of a soluble factor. In contrast to bone stromal cells isolated from normal controls, stromal cells isolated from morphologically normal bone in one patient with Paget's disease also stimulated osteoclast formation in this way; this osteoclastogenesis was inhibited by OPG. Our results indicate that Paget's bone stromal cells support osteoclast formation by a RANKL-dependent process which involves not only cell-cell contact but also secretion of soluble RANKL.